UJI TAKARAN PUPUK KANDANG SAPI TERHADAP TIGA VARIETAS WIJEN (Sesamum indicum L.) - Susilo, Eko; Nurhayati, Dewi Ratna; Bahri, Saiful (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2021)
Sesame (Sesamum indicum L.) is one of the plantation crop commodities which has high economic value (Rusmin, 2007). Sesame (Sesamum indicum L.) is classified as a high quality food and edible oil because of its high mineral and protein content and low saturated fatty acid content, so it does not have a negative impact on health (Winarno, 1993). With an intercropping cropping pattern, the yield of sesame plants in Indonesia is still low, namely an average of 350 kg / ha of dry seeds (Rukmana, 1998). The shortage of domestic sesame products is met with imports of sesame from Thailand, Vietnam and other countries (Hanura, 2004). This proves that the opportunity to develop sesame is still very open. The main obstacle in sesame development is the low yield. One way to increase productivity is by means of fertilization. The purpose of this study was to determine the effect of cow manure and its interaction on the growth and yield of sesame. The research was conducted in Pijiharjo Hamlet, Karang Lor Village, Manyaran District, Wonogiri Regency, Central Java (57662), from 19 April to 16 July 2020.This research is a factorial experiment consisting of two factors based on a completely randomized block design (RAKL) consisting of 3 replications. The treatment is as follows: the first factor is the provision of cow manure at a rate of 150 gr (P2), 100 gr (P1) and without fertilizer (P0) as a control. The second factor is three kinds of sesame varieties consisting of SBR 1 (V1), SBR 4 (V2) and WINAS 1 (V3). Based on the results of research and discussion, it can be concluded that: The three varieties of sesame are not responsive to the three treatments of the dose of cow manure so that there is still a need to add a more precise dose according to the needs of the sesame plant.